Measuring access to contraceptive methods by ethnic groups in Colombia using small areas estimation - Lina María Sánchez-Céspedes; Juan Sebastián Oviedo-Mozo; Juliana Guerrero; Carlos Arturo Ramirez-Hernandez (Cadernos de Saúde Pública)
Abstract: Afro-descendant and Indigenous women face limited access to contraceptives due to contextual barriers, partner disapproval, and educational gaps. One major challenge in designing policies to facilitate access to safe, effective, acceptable, and affordable contraceptive methods for these groups is the lack of data for informed decision-making by national and local governments. To address this information gap, we propose using small area estimation (SAE) focusing on population and ethnic groups rather than geographic areas. We estimated four state-level indicators for women by ethnic group: unmet need for family planning, family planning need satisfied, contraceptive prevalence rate, and modern contraceptive prevalence rate. SAE yielded consistent estimates with mean square errors mostly below 1% of the estimated values at both state and ethnic group levels. Contraceptive prevalence rates among Indigenous, afro-descendant, and non-ethnic women (who do not self-identify with an ethnic group) were 70.6%, 76.6%, and 81.7%, respectively. Lower contraceptive use is not determined by ethnicity. Being in a relationship increases the likelihood of contraceptive use; however, when afro-descendant and Indigenous women have partners from the same ethnic background this probability decreases. Consequently, addressing disparities in contraceptive use among ethnic groups requires government initiatives involving both women’s partners and communities.